Handbook of fingerprint recognition - Maltoni, Davide (Springer, 2009)
Provides coverage of the major concepts, topics, and security methods associated with fingerprint recognition. This work features chapters covering sensor technology, performance evaluation, standards, and securing fingerprint systems. It is suitable for biometric security professionals, researchers, developers and systems administrators.- Resumé vydavatel
Previous edition: 2003.
Keywords: biometrická identifikace; biometrika; otisky prstů; daktyloskopie; rozpoznávání vzorů; zpracování obrazu; automatická identifikace; algoritmy; výpočetní metody; matematické modelování; biometric identification; biometry; fingerprints; dactyloscopy; pattern recognition; image processing; automatic identification; algorithms; computational methods; mathematical modeling; elektronické knihy; příručky; electronic books; handbooks and manuals